Oral delivery of Bacillus subtilis spores expressing cysteine protease of Clonorchis sinensis to grass carp (Ctenopharyngodon idellus): Induces immune responses and has no damage on liver and intestine function. Issue 64 (May 2017) - Tang, Zeli; Sun, Hengchang; Chen, TingJin; Lin, Zhipeng; Jiang, Hongye; Zhou, Xinyi; Shi, Cunbin; Pan, Houjun; Chang, Ouqin; Ren, Pengli; Yu, Jinyun; Li, Xuerong; et al.
Abstract: Clonorchis sinensis ( C. sinensis ) is a fish-borne trematode. Human can be infected by ingestion of C. sinensis metacercariae parasitized in grass carp ( Ctenopharyngodon idella ). For induction of effective oral immune responses, spores of Bacillus subtilis ( B. subtilis ) WB600 were utilized as vehicle to delivery Cs CP (cysteine protease of C. sinensis ) cooperated with CotC ( B.s -CotC-CP), one of coat proteins, to the gastrointestinal tract. After routine culture of 8–12 h in LB medium, B. subtilis containing CotC- Cs CP was transferred into the sporulation culture medium. SDS-PAGE, western blotting and the growth curve indicated that the best sporulation time of recombinant WB600 was 24–30 h at 37 °C with continuous shaking (250 rpm). Grass carp were fed with three levels of B.s -CotC-CP (1 × 10 6, 1 × 10 7, and 1 × 10 8 CFU g −1 ) incorporated in the basal pellets diet. The commercial pellets or supplemented with spores just expressing CotC (1 × 10 7 CFU g −1 ) were served as control diet. Our results showed that grass carp orally immunized with the feed-based B.s -CotC-CP developed a strong specific immune response with significantly ( P < 0.05) higher levels of IgM in samples of serum, bile, mucus of surface and intestinal compared to the control groups. Abundant colonization spores expressing Cs CP were found in hindgut that is conducive to absorption and presentation of antigen. Moreover, B. subtilis spores appeared to show no sign of toxicity or damage in grass carp. Our cercariae challenge experiments suggested that oral administration of spores expressing Cs CP could develop an effective protection against C. sinensis in fish body. Therefore, this study demonstrated that the feed-based recombinant spores could trigger high levels of mucosal and humoral immunity, and would be a promising candidate vaccine against C. sinensis metacercariae formation in freshwater fish. Highlights: Construction of Bacillus subtilis spore expressing Cs CP with high positive rate. Screening of the optimum sporulation conditions to express CotC- Cs CP on spores. Recombinant spores can significantly enhance immune responses of grass carp. Recombinant spores can colonize with no Cs CP degradation in hindgut of fish. Spores expressing Cs CP developed an effective protection against C. sinensis in fish.